Buoyancy-driven destabilization of an immersed granular bed. (26th March 2018) - Herbert, Eric; Morize, Cyprien; Louis-Napoléon, Aurélie; Goupil, Christophe; Jop, Pierre; D'Angelo, Yves
Abstract : Under suitable conditions, an immersed granular bed can be destabilized by local thermal forcing and the induced buoyant force. The destabilization is evident from the triggering and establishment of a dense fluid-like granular plume. Varying the initial granular layer average height $h$, a time series of the free layer surface is extracted, allowing us to dynamically compute the underlying volume of the granular layer. Different observed phenomena, namely the initial interface deformation, the lowering of the average granular interface (i.e. decrease of the granular layer volume) and the emission of a plume, are analysed. We show that the phenomenon is mainly driven by heat transfer, for large $h$ and also involves a variable height thermal boundary condition and Darcy flow triggering, for small $h$ . Simple modelling with no adjustable parameters not only allows us to capture the observed scaling power laws but is also in quantitative agreement with the obtained experimental data.